Behaviour of aluminium alloy structures under fire - Faggiano, Beatrice; De Matteis, Gianfranco; Landolfo, Raffaele; Mazzolani, Federico M. (Journal of Civil Engineering and Management, 2004)
In the paper the attention is focused on the influence of high temperatures on the mechanical properties of the aluminium alloys selected by Eurocode 9 for structural uses. Therefore, based on the analysis of existing data taken from technical literature, the variation of the Young's modulus, the conventional yielding strength, the ultimate strength, the hardening factor and the material ultimate strain are represented as a function of the temperature. A mechanical model, based on the well‐known Ramberg‐Osgood formulation, which appropriately takes into account the peculiarities of such materials at high temperatures, is provided. In particular, the combined influence of the hardening factor and temperature on the material stress‐strain relationship is considered and analysed. Then, the proposed model has been introduced in a finite element program, devoted to the global analysis of structures under fire. Finally, the results obtained for a simple portal frame structure, designed with different aluminium alloys, are presented, showing the valuable effect of the material modelling on the structural behaviour of aluminium structures under fire.First Published Online: 14 Oct 2010